2014
DOI: 10.1038/ki.2014.188
|View full text |Cite
|
Sign up to set email alerts
|

A useful scoring system for the prediction and management of delayed graft function following kidney transplantation from cadaveric donors

Abstract: Delayed graft function (DGF) is a common complication in kidney transplantation and is known to be correlated with short- and long-term graft outcomes. Here we explored the possibility of developing a simple tool that could predict with good confidence the occurrence of DGF and could be helpful in current clinical practice. We built a score, tentatively called DGFS, from a French multicenter and prospective cohort of 1844 adult recipients of deceased donor kidneys collected since 2007, and computerized in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 46 publications
(64 reference statements)
2
91
5
Order By: Relevance
“…A recent randomized trial showed that 31.5% of patients in an ATG group developed DGF compared with 44.6% using anti-interleukin 2 receptor antibody treatment. Chapal et al also found five explicative variables that contributed significantly to DGF prediction, and demonstrated that risk of DGF was reduced 1.73-fold in patients with ATG [6]. Other studies also demonstrated significantly lower rates of DGF in ATG-induced DCD recipients [24][25][26].…”
Section: Discussionmentioning
confidence: 85%
“…A recent randomized trial showed that 31.5% of patients in an ATG group developed DGF compared with 44.6% using anti-interleukin 2 receptor antibody treatment. Chapal et al also found five explicative variables that contributed significantly to DGF prediction, and demonstrated that risk of DGF was reduced 1.73-fold in patients with ATG [6]. Other studies also demonstrated significantly lower rates of DGF in ATG-induced DCD recipients [24][25][26].…”
Section: Discussionmentioning
confidence: 85%
“…In fact, none of the available predictive models includes in final formula variables reflecting donor maintenance. Except for terminal serum creatinine (that could reflect renal consequences of hypovolemia, shock and other causes of acute kidney injury), only the score developed by Chapal et al analyzed some variable related to donor care (type of vasopressor) [24].…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Jeldres et al [18] proposed a simpler model requiring 6 variables based on the Canadian population. Furthermore, the French multicenter study group also designed a score [19] (called DGFS; www.divat.fr/en/online-calculators/dgfs) by using 5 variables. These models used only pre-implantation risks to predict DGF.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the importance of early detection of DGF in KT, several previous studies had developed models for predicting the likelihood of DGF [16][17][18][19]. These predicting models mostly used pre-implantation risk factors to forecast DGF.…”
Section: Introductionmentioning
confidence: 99%